Ionically Generated Built‐In Equilibrium Space Charge Zones—a Paradigm Change for Lead Halide Perovskite Interfaces. (26th May 2020) - Kim, Gee Yeong; Senocrate, Alessandro; Moia, Davide; Maier, Joachim
Abstract: Methylammonium lead iodide (MAPI) is the archetype of the intensively researched class of perovskites for photovoltaics. Nonetheless, even equilibrium aspects are far from being fully understood. Equilibrium space charge effects at the MAPI/TiO2 and MAPI/Al2 O3 interfaces are discussed, which are of paramount significance for solar cells. Different from the photovoltaic literature in which such built‐in potentials are considered as being generated solely by electronic charge carriers, a generalized picture that considers the equilibrium distribution of both ionic and electronic carriers is applied. Experimental evidence is given that shows it is the ions that are responsible for the equilibrium space charge potential, the reason being a pronounced ion adsorption at the contacts. The electronic redistribution is a sheer consequence of the so‐established electric field. Experiments with mesoporous oxide as well as experiments with MAPbBr3 (MAPBr) indicate photovoltaic relevance and material generality in terms of the choice of the lead‐based perovskite. The occurrence of space charge effects at heterojunctions generated by ionic redistribution is not only a novel concept in photovoltaics, it also provides a new path to modifying charge‐selective interfaces, as well as a better understanding of the behavior in mesoporous systems. Abstract : Equilibrium contacts in photovoltaics such as heterojunctions of CH3 NH3 PbI3 (MAPI) with oxides are usually discussed in terms of electronic effects only. Here, evidence for ionically dominated interfacial situations for MAPI/TiO2 and MAPI/Al2 O3 is given, which slave the electronic carriers. The influence of such ionic adsorption layers (most probably Pb 2+ ) under operational conditions is also discussed.